Perancangan Aplikasi Pemesanan Air Galon Isi Ulang Berbasis Mobile - Babako, Wiki Siam; Sitokdana, Melkior N. N. (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Drinking water depot (DAM) is a business that is run through the process of treating ordinary water into water that can be consumed and sold to consumers. In order for the goal to be achieved, the owner of the drinking water depot needs an application that can help with marketing and promotion. Therefore, researchers designed an application called the GaGas application which stands for gallons and gas, besides that gagas in the Dayak Kanayatn language means good, charming, and good. The method used in this study is a descriptive method, by describing and interpreting objects according to existing conditions. In software development using the prototype method. Application testing uses the Black Box Testing method which is carried out to find every error in the application. In the test results using the Black Box Testing method, it was found that the suitability of the expected results was found, with the results that have been obtained, it can be concluded that the application 1has very few / minimal system errors or bugs.